3D-COFORM: Making 3D documentation an everyday choice for the cultural heritage sector - Denis Pitzalis; Jaime Kaminski; Franco Niccolucci (Virtual Archaeology Review)
This paper provides an overview of the 3D-COFORM project which began in December 2008 and aims to advance the state-of-the-art in 3D-digitsation and make 3D-documentation an everyday practical choice for digital documentation campaigns in the cultural heritage sector.